SPIRAL COMPUTED TOMOGRAPHY IN DETERMINING THE PARAMETERS OF LAPAROTOMY TO THE ABDOMINAL ORGANS - Данильченко, Иван Юрьевич; Развозжаев, Юрий Борисович; Лещишин, Ярослав Миронович; Савостьянов, Илья Васильевич; Алонцев, Андрей Владимирович (Medicine in Kuzbass, 2019)
Objective – to justify the use of spiral computed tomography in determining the parameters of laparotomy to the abdominal organs.Materials and methods. On spiral computer tomograms of the abdominal cavity of 71 patients evaluated, the upper transverse, and median total average median laparotomy. The anatomical study was carried out – on 25 corpses the parameters of the upper transverse laparotomy were evaluated, on 14 corpses the parameters of total median laparotomy were evaluated.Carried out the measurement of the angle of operative activity along the length, the angle of operative activity by the width of the angle of the axis of operative activity, the depth of the wound.The right and left domes of the diaphragm, the esophageal orifice of the diaphragm, the right and left iliac fossa and the rectal fossa were chosen as points of application.Results. Upper transverse laparotomy, both according to spiral computed tomography, and according to anatomical studies, the set of parameters has more favorable conditions to the points of the upper floor of the abdominal cavity. Total median laparotomy on a set of parameters, both in the anatomical study and according to spiral computed tomography has more favorable conditions to the points of the lower floor of the abdominal cavity. The average median laparotomy, of all three approaches, according to spiral computed tomography, has the least favorable conditions to almost all points of the application.Differences in the anatomic study and data from spiral CT due to the peculiarities of measurement and small sample volume of anatomical studies.Conclusions. Spiral computed tomography allows a comparative assessment of the parameters of laparotomic approaches. Upper transverse laparotomy has more favorable conditions to the points of the upper floor of the abdominal cavity. Total median laparotomy has more favorable conditions to the points of the lower floor of the abdominal cavity.
Keywords: parameters of surgical accesses; laparotomy; spiral computed tomography